Balitanay's laktob a Kalinga weaving story - Albert, Reynalyn; Salvador-Amores, Analyn V. (University of the Philippines Baguio, 2020)
This story is inspired by the remaining master weavers in Naneng, Kalinga. The master weavers are now currently teaching young women on how to weave the laktob and gitot by using the traditional backstrap loom.